Investigation of guided wave propagation in pipes fully- and partially-embedded in concrete - Leinov,E; Lowe,MJS; Cawley,P (The Journal of the Acoustical Society of America, 2016)
The application of long-range guided-wave testing to pipes embedded in concrete results in unpredictable test-ranges. The influence of the circumferential extent of the embedding-concrete around a steel pipe on the guided wave propagation is investigated. An analytical model is used to study the axisymmetric fully embedded pipe case, while explicit finite-element and semi-analytical finite-element simulations are utilised to investigate a partially embedded pipe. Model predictions and simulations are compared with full-scale guided-wave tests. The transmission-loss of the T(0,1)-mode in an 8 in. steel pipe fully embedded over an axial length of 0.4 m is found to be in the range of 32–36 dB while it reduces by a factor of 5 when only 50% of the circumference is embedded. The transmission-loss in a fully embedded pipe is mainly due to attenuation in the embedded section while in a partially embedded pipe it depend strongly on the extent of mode-conversion at entry to the embedded-section; low loss modes with energy concentrated in the region of the circumference not-covered with concrete have been identified. The results show that in a fully embedded pipe, inspection beyond a short distance will not be possible, whereas when the concrete is debonded over a fraction of the pipe circumference, inspection of substantially longer lengths may be possible.